The Design of Electro Cardiograph Signal Generator Using IC 14521 and IC 14017 - Wijaya, Nur Hudha; Arif Rijali, Wahidun; Shahu, Nishith; Ahmad, Irfan; Andri Atmoko, Rachmad (Journal of Robotics and Control (JRC), 2021)
ECG or Electrocardiograph is a tool to find out the electrical activity of the heart in patients. Electrocardiogram (ECG) is a graphic result records electrical potential resulting from by heartbeat, (Mervin J. Goldman, 1990). ECG recording very useful to know present certain hypertrophy, arrhythmia, pericarditis, for example potassium electrolyte disturbances. Tool this be named generator signal ECG. Tool the generator signal ECG functioning for produce the signal Electric heart in adult patient sand to check ECG error or no. So that it can ease technical electro medic in maintenance medical equipment periodically. The tool utilizes IC 14521 as oscillator or signal generator and using IC 14 017 as a shift register who has responsibility to remove from pin 1 to pin the other. The benefits of the ECG signal generating device so that technical electro medic easy and not difficult in check ECG without must using patients. So this tool as a form clone of the human heart. The tool such as a patient simulator. Based on the results of laboratory tests that have been done with the author concluded that, ECG signal generating device to function properly so that produce form of mock patient's heart signal that shown monitored oscilloscope in the waveform display P, Q, R, S, T.